2012
DOI: 10.2308/isys-50331
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Audit Function in Information Technology Governance: A Holistic Perspective

Abstract: The internal audit function's (IAF) role has evolved from traditional (accounting and financial control) to more strategic (governance). The business environment has changed as well, and nowadays relies considerably on information technology (IT). Only a few studies have investigated IT governance from a holistic perspective. Further, no study has closely examined IAF involvement in IT governance as a whole. This study uses a holistic approach to describe IAF involvement in IT governance and to explore the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The IAF should play an active role in information security governance and enterprise risk management efforts with respect to information security (Arena et al, 2010;Busco, Giovannoni, Riccaboni, Frigo, & Scapens, 2006;Havelka & Merhout, 2013;Héroux & Fortin, 2013;Merhout & Havelka, 2008;Stoel et al, 2012). According to COBIT5 (ISACA, 2012a), the regular monitoring of performance (Process MEA01) and independent auditing of security (Process MEA02) are an important part of these governance efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The IAF should play an active role in information security governance and enterprise risk management efforts with respect to information security (Arena et al, 2010;Busco, Giovannoni, Riccaboni, Frigo, & Scapens, 2006;Havelka & Merhout, 2013;Héroux & Fortin, 2013;Merhout & Havelka, 2008;Stoel et al, 2012). According to COBIT5 (ISACA, 2012a), the regular monitoring of performance (Process MEA01) and independent auditing of security (Process MEA02) are an important part of these governance efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The first sees internal auditing as a career in itself, whereas the second views it as a training ground for top managers, an aspect that could fall under the category of internal audit's other roles. Héroux and Fortin (), adopting a holistic approach to examining IT governance, found that the IAF focuses on risk assessment and evaluation of IT controls. Along those lines, D'Onza, Lamboglia, and Verona () argued that managers want greater support from the IAF for IT governance.…”
Section: The Multiple Roles Of Internal Auditmentioning
confidence: 99%
“…To be able to detect material weaknesses in IT systems, audit teams need to have knowledge and competencies not only about accounting and auditing, but also on IT specialised knowledge. Specialised IT professional qualifications and certifications have been shown to have more likelihood of involvement with auditing on IT governance, risks and controls (Héroux and Fortin, 2012). Knowledge about IT and accounting system, are shown to be important factors in IT audit quality (Havelka and Merhout, 2013;Stoel, Havelka, and Merhout, 2012).…”
Section: Audit Team's It Knowledge and Competenciesmentioning
confidence: 99%